The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, a; Rodà, F (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, A.; Roda, F. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
The following values have no corresponding Zotero field: accession-num: 12670768
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

Land use changes, natural regeneration patterns, and restoration practices after a large wildfire in NE Spain: Challenges for fire ecology and landscape restoration - ESPELTA, J M; Rodrigo, a; Habrouk, A; Meghelli, N; Ordonez, J L; RETANA, J (FIRE AND BIOLOGICAL PROCESSES, 2002)
Great wildfires have recently affected sub-Mediterranean areas of central Catalonia (NE Spain). The large extension of the burned areas, as well as the fact that non-fire-prone vegetation has been severely affected, lead to ponder over the natural regeneration patterns occurring, and over the best strategies to restore and manage the burned areas. In the present study, we review the land use changes and the natural regeneration patterns observed after the large wildfire that occurred in Bages-Bergueda in 1994. The fire resulted in: (i) the creation of new croplands and pastures in previously forested areas, (ii) the expansion of mixed oak (Quercus ilex and Q. cerrioides) coppices, (iii) the failure of natural regeneration of the dominant tree species (Pinus nigra), leading to the appearance of areas without any tree regeneration. In this context, we discuss the results of different experiments carried out to reforest P nigra stands and to ameliorate the structure of mixed oak coppices.
Keywords: land use changes; Mediterranean areas; natural regeneration; Spain; wildfires

Nitrogen deposition in Mediterranean forests. - Rodà, F; Avila, a; Rodrigo, a (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

metal contents in Parmelia caperata(L.) Ach. compared to bulk deposition, throughfall and leaf-wash fluxes in two holm oak forests in Montseny (NE Spain) - Rodrigo, a; Avila, a; Gómez-Bolea, A (Atmospheric Environment, 1999)
The metal concentrations of V, Cr, Co, Ni, Cu, Zn, Cd, Hg and Pb were analysed in distilled water extracts of Parmelia caperata and in bulk deposition, throughfall and an experimental in situ washing of leaves at two forests at Montseny (NE Spain) submitted to di¤erential exposure to the industrial and tra¦c activities around Barcelona. Lichen concentra- tions of Zn, Cu, V, and Cd were higher at the site of greater exposure to pollutants. Consistently, there was higher dry deposition of these metals at the more exposed site. The order of abundance of trace metals in the lichen was similar to that in the deposition variables, although Pb and Cu had intermediate concentrations in the lichen but were very low in the deposition measurements. This indicated the higher a¦nity of Pb and Cu for the exchange sites in the lichen cell wall and the fact that lichens accumulated Pb for the last 12Ð18 y when emissions were much higher than today. The ability of Parmelia caperata to indicate the deposition of heavy metals, together with its easy sampling and handling, its broad distribution and its easy identiÞcation suggest that the lichen extract procedure described here could be used to establish gradients of atmospheric deposition of heavy metals at a general geographic level
Keywords: atmospheric deposition; bulk deposition; parmelia caperata; Quercus ilex; throughfall; trace metal